Development, management, and resolution of biliary complications after living and deceased donor liver transplantation: A report from the adult‐to‐adult living donor liver transplantation cohort study consortium. Issue 3 (11th March 2013) - Zimmerman, Michael A.; Baker, Talia; Goodrich, Nathan P.; Freise, Chris; Hong, Johnny C.; Kumer, Sean; Abt, Peter; Cotterell, Adrian H.; Samstein, Benjamin; Everhart, James E.; Merion, Robert M.
<x xml:space="preserve">Abstract</x> Adult recipients of living donor liver transplantation (LDLT) have a higher incidence of biliary complications than recipients of deceased donor liver transplantation (DDLT). Our objective was to define the intensity of the interventions and the time to resolution after the diagnosis of biliary complications after liver transplantation. We analyzed the management and resolution of posttransplant biliary complications and investigated the comparative effectiveness of interventions in LDLT and DDLT recipients. For the analysis of biliary complications (leaks or strictures), we used a retrospective cohort of patients who underwent liver transplantation at 8 centers between 1998 and 2006 (median follow‐up from onset=4.7 years). The numbers, procedure types, and times to resolution were compared for LDLT and DDLT recipients. Posttransplant biliary complications occurred in 47 of the 189 DDLT recipients (25%) and in 141 of the 356 LDLT recipients (40%). Biliary leaks constituted 38% of the post‐DDLT biliary complications (n=18) and 65% of the post‐LDLT biliary complications (n=91). The median times to first biliary complications were similar for DDLT and LDLT (11 versus 14 days for leaks, P=0.63; 69 versus 107 days for strictures, P=0.34). Overall, 1225 diagnostic and therapeutic procedures, including reoperation and retransplantation, were performed (6.5±5.4 per recipient; 5.5±3.6 for DDLT versus 6.8±5.8 for LDLT, P=0.52). The median number of months to the resolution of a biliary complication (i.e., a tube‐, stent‐, and drain‐free status) did not significantly differ between the DDLT and LDLT groups for leaks (2.3 versus 1.3 months, P=0.29) or strictures (4.9 versus 2.3 months, P=0.61). Although the incidence of biliary complications is higher after LDLT versus DDLT, the treatment requirements and the time to resolution after the development of a biliary complication are similar for LDLT and DDLT recipients. Liver Transpl 19:259–267, 2013. © 2013 AASLD.